2021
DOI: 10.1371/journal.pone.0260533
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of breast tumor drug resistance by 2,3,5,4’-tetrahydroxystilbene for exhibition synergic chemotherapeutic effect

Abstract: Chemotherapy drugs have limited efficacy in breast cancer due to multidrug resistance generated by cancer cells against anticancer drugs. In this study, we developed a novel derivative, 2, 3, 5, 4‘-tetrahydroxystilbene (TG1) by modifying 2, 3, 5, 4‘-tetrahydroxystilbene-2-O-beta-D-glucoside (THSG). In-vivo zebrafish embryo tests revealed that TG1 showed low toxicity. The equitoxic combination of DOX or DTX with TG1 in MCF-7/Adr reduced the IC50 of DOX or DTX, and the combination index (CI) showed strong synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Natural products are important sources of innovative drug development [38], but clinical applications are limited due to poor bioavailability or severe toxicity [39]. TG1, modified from 2,3,5,4tetrahydroxystilbene-2-O-β-D-glucoside (THSG) via deglucosylation, has been proven to have low toxicity in vitro and in vivo, while this modification may improve the drug potency via the reduction of the drug efflux effect [30]. Further, our results found that the cytotoxic effect of TG1 on CRC cells does not only come from inducing apoptosis, but more importantly, it regulates the induction of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products are important sources of innovative drug development [38], but clinical applications are limited due to poor bioavailability or severe toxicity [39]. TG1, modified from 2,3,5,4tetrahydroxystilbene-2-O-β-D-glucoside (THSG) via deglucosylation, has been proven to have low toxicity in vitro and in vivo, while this modification may improve the drug potency via the reduction of the drug efflux effect [30]. Further, our results found that the cytotoxic effect of TG1 on CRC cells does not only come from inducing apoptosis, but more importantly, it regulates the induction of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A new small molecule drug called TG1 has been developed for versatile drug applications. It has been shown to have low toxicity and promote cytotoxicity in breast cancer cells when used in combination with chemotherapeutic drugs [30]. However, until now, the role of TG1 in inducing cytotoxic effects on CRC and the underlying mechanisms and downstream signaling have been unknown.…”
Section: Introductionmentioning
confidence: 99%